Parents' perception of coach behaviors in youth sports in Iceland - Andrea Líf Wender 1998-; Stefán Óli Þorleifsson 1995- (2022)
Background: Recent studies have focused on mental health among athletes and prior research have found a link between emotional abusive coach behaviors and mental health issues among athletes. Little is known about the prevalence of emotional abusive coach behaviors in Iceland. Aims: Firstly, to examine parental perception of coach behaviors in youth sports, and to explore if parents are aware of how the coaches behave within the sports environment. Secondly, we wanted to examine the difference between parental perception of coach behaviors of children aged 6-10 and children aged 11-14. Finally, we wanted to explore if the code of conduct for coaches set forth by the National Olympic and Sports Association of Iceland are being followed by the coaches. Method: Participants included 345 parents (275 mothers and 70 fathers) of children aged 6 to 14. Parents answered a survey based on questionnaires by Strand (2021) and Newton et al. (2000) and definition of emotional abusive coach behaviors by Stirling (2013), Doyle (1997), Gervis and Dunn (2004), Garbarino et al. (1986), Kirby et al. (2000), Stirling and Kerr (2008), and Strand (2021). Descriptive statistics was used to examine the prevalence of emotional abusive coach behaviors and code of conduct for coaches. To examine the difference between the age groups, Pearson Chi square tests were conducted. Results: According to the descriptive statistics, the rate of which parents had witnessed an emotional abusive coach behavior was relatively low. Furthermore, it was the parents’ perception that coaches are behaving in line with the code of conduct put forth by the National Olympic and Sports Association of Iceland. Finally, no significant differences were observed in responses to emotional abusive coach behaviors, positive coach behaviors, and code of conduct for coaches between parents of children aged 6-10 and parents of children aged 11-14. Conclusion: The prevalence of emotional abusive coach behaviors in Iceland is quite low within youth sports. Furthermore, ...